Determination of kinetic parameters of N-vinylpyrrolidone radical polymerization in water by Pulsed Electron Polymerization−Size Exclusion Chromatography (PEP−SEC). (January 2023) - Sawicki, Piotr; Łapienis, Grzegorz; Kadłubowski, Sławomir; Ulański, Piotr; Rosiak, Janusz M.
Abstract: Propagation step of radical polymerization of N -vinylpyrrolidone (NVP) in aqueous solutions has been studied by a recently introduced method, Pulsed Electron Polymerization−Size Exclusion Chromatography (PEP−SEC). Propagation rate constants have been determined at various initial monomer concentrations and reaction temperatures. It has been shown that the kinetic data, their concentration dependence, activation energy ( E a ) and preexponential factor ( A ) in the Arrhenius equation obtained by PEP−SEC are very similar to those obtained by the well-established Pulsed Laser Polymerization−Size Exclusion Chromatography (PLP−SEC). These results support the correctness of the new PEP−SEC technique, which is expected to have some advantages over the classical PLP−SEC, in particular by its applicability to studying polymerization in nontransparent systems and lack of any chemical initiators and can be developed into a method alternative or complementary to PLP−SEC.